Ten years of soil CO2 continuous monitoring on Mt. Etna: Exploring the relationship between processes of soil degassing and volcanic activity. (9th August 2013) - Liuzzo, Marco; Gurrieri, Sergio; Giudice, Gaetano; Giuffrida, Giovanni
Abstract : [1] The measurement of soil CO2 flux variations is a well−established practice in many volcanic areas around the world. Until recently, however, most of these were made using direct sampling methods. These days, a variety of automatic devices providing real‐time data now make the continuous monitoring of volcanic areas possible. A network of automatic geochemical monitoring stations (EtnaGas network) was developed by INGV Palermo and installed at various sites on the flanks of Mt. Etna. Here, we present a large set of soil CO2 flux data recorded by the network, dating back 10 years, a period in which several noteworthy eruptive phenomena occurred. Our statistical analysis strongly suggests that anomalous measurements of soil CO2 flux are attributable to volcanic origin and in almost all cases precede volcanic activity. Here, we present the actual data series recorded by EtnaGAS and an interpretative model of the expected behavior of soil CO2 flux (in terms of increase‐decrease cycles), which corresponded well with the volcanic activity during this period. Through the use of a comparative approach, incorporating both volcanological and geochemical data, the global soil CO2 flux trends are put into a coherent framework, highlighting close links between the time flux variations and volcanic activities. These insights, made possible from 10 years of uninterrupted data, confirm the importance of continuous monitoring of volcanic soil degassing, and may contribute in the forecasting of imminent eruptive activity or the temporal evolution of an in‐progress eruption, therefore facilitating Civil Defense planning in volcanic areas under high‐hazard conditions. Key Points: Clear relationship between anomalous soil CO2 degassing and volcanic activity Cycles of CO2 increase‐decrease always anticipated the eruptive activity Brief lava fountaining episodes were preceded by minor increase‐decrease cycles